2008
DOI: 10.4314/ejesm.v1i1.41567
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous uses of plant leaves to treat malaria fever at Omo Forest reserve (OFR) Ogun state, Nigeria.

Abstract: The indigenous uses of forest plant leaves by the enclave dwellers of Omo forest reserve (OFR) Ogun state, Nigeria were investigated to provide further information on the traditional uses of environmental resources such as the forest in healthcare delivery systems. This is in response to the recent upsurge search for alternative systems of medicare to combat infectious diseases like malaria. Well structured and pretested questionnaire were administered through interview schedules on some randomly selected encl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 0 publications
7
12
0
Order By: Relevance
“…Trees were found to be the most used plants followed by climber, then bulb and shrub. Plants are important in traditional treatment of various diseases including depression (Adekunle, 2008). The results of this survey showed that majority (90%) of the herb sellers/traditional medical practitioners (TMPs)/ herbalists claimed no occurrence of side effects following patients' use of herbal preparations.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Trees were found to be the most used plants followed by climber, then bulb and shrub. Plants are important in traditional treatment of various diseases including depression (Adekunle, 2008). The results of this survey showed that majority (90%) of the herb sellers/traditional medical practitioners (TMPs)/ herbalists claimed no occurrence of side effects following patients' use of herbal preparations.…”
Section: Discussionmentioning
confidence: 93%
“…The results of this survey showed that majority (90%) of the herb sellers/traditional medical practitioners (TMPs)/ herbalists claimed no occurrence of side effects following patients' use of herbal preparations. Some of the plants revealed in the survey have been cited in the ethnobotanical survey of some African countries (Jinju, 1990;Ayodele, 2005;Adekunle, 2008;Ajayeioba and Ogbole, 2010;Soladoye et al, 2010;Idowu et al, 2010;Oni, 2010) for other disease conditions. Thus, scientific studies on these plants would provide insights into their potentials and understanding the pharmacological actions of the active compounds found in them (Ramana, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The plant leaves are important ingredient in traditional treatment of various diseases as it occurred as a component in many herbal preparations. 21 Majority of the herbal recipes were observed to be polyherbal (i.e. in combination), while some were prepared from single plant source.…”
Section: Discussionmentioning
confidence: 99%
“…Plant leaves are important ingredient in traditional treatment of the disease as it featured as a component in many herbal preparations which is in agreement with previous reports. 28,29 The leaves, stems, barks, roots and seeds of the recommended plants are used preferably when fresh than when dry. The preparations are administered mainly as infusion, decoction or powder.…”
Section: Ethnomedicinal Plantsmentioning
confidence: 99%